Globalizacja i konsumpcjonizm w natarciu. Uwagi na temat skutków zmian modernizacyjnych w dolinie Nilu północnego Sudanu - Kurcz, Maciej (Studia Etnologiczne i Antropologiczne, 2017)
The article—deeply based on the field observations—deals with the proces of globalization in Northern Sudan, focusing particularly on infrastructural changes and their results in the second decade of the 21st century. Scholars—starting with the book by Jeremi Prestholdt (2008), who imported history of consumption and consumerism into the African studies—are currently debating over the character and impact of globalization. Using this approach, the article addresses the question about what needs some of the imported goods satisfy, how African consumers deal with these objects, and finally how these objects become incorporated into the local culture system.